2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

Valence-state analysis through spectroelectrochemistry in a series of quinonoid-bridged diruthenium complexes [(acac)(2)Ru(mu-L)Ru(acac)(2)](n) (n =+2,+1, 0,-1,-2) - Ghumaan, Sandeep; Sarkar, Biprajit; Maji, Somnath; Puranik, Vedavati G.; Fiedler, Jan; Urbanos, Francisco A.; Jimenez-Aparicio, Reyes; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry-A European Journal, 2008)
The quinonoid ligand-bridged diruthenium compounds [(acac)(2)Ru(mu-L2-)Ru(acac)(2)] (acac(-) = acetylacetonato = 2,4-pentanedionato; L2- = 2,5-dioxido-1,4-benzoquinone, 1; 3,6-dichloro-2,5-dioxido-1,4-benzoquinone, 2; 5,8-dioxido-1,4-naphthoquinone, 3; 2-3-dichloro-5,8-dioxido-1,4-naphthoquinone, 4; 1,5-dioxido-9,10-anthraquinone, 5; and 1,5-diimido-9,10-anthraquinone, 6) were prepared and characterized analytically. The crystal structure analysis of 5 in the rac configuration reveals two tris(2,4-pentanedionato)ruthenium moieties with an extended anthracenedione-derived bis(ketoenolatee) pi-conjugated bridging ligand. The weakly antiferro-magnetically coupled {Ru-III(mu-L2-)Ru–(III)} configuration in 1-6 exhibits complicated overall magnetic and EPR responses,. ne simultaneous presence of highly redox-active quinonoid-bridging ligands and of two ruthenium centers capable of adopting the oxidation states +2, +3, and +4 creates a large variety of possible oxidation state combinations. Accordingly. the complexes 1-6 exhibit two reversible one-electron oxidation steps and at least two reversible reduction processes. Shifts to positive potentials were observed on introduction of Cl substituents (1 -> 2, 3 -> 4) or through replacement of NH by O (6 -> 5). The ligand-to-metal charge transfer (LMCT) absorptions in the visible region of the neutral molecules become more intense and shifted to lower energies on stepwise reduction with two electrons. On oxidation, the para-substituted systems 1-4 exhibit monocation intermediates with intervalence charge transfer (IVCT) transitions of (RuRuIV)-Ru-III mixed-valent species. In contrast, the differently substituted systems 5 and 6 show no such near infrared (NIR) absorption. While the first reduction steps are thus assigned to largely ligand-centered processes, the oxidation appears to involve metal-ligand delocalized molecular orbitals with variable degrees of mixing.
Keywords: magnetic properties; quinones; ruthenium; spectroelectrochemistry; structure elucidation; valence-state distributions

Strong metal-metal coupling in mixed-valent intermediates [Cl(L)Ru(mu-tppz)Ru(L)Cl](+), L = beta-diketonato ligands, tppz=2,3,5,6-tetrakis(2-pyridyl)pyrazine - Kundu, Tanaya; Schweinfurth, David; Sarkar, Biprajit; Mondal, Tapan Kumar; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
Five diruthenium(II) complexes [Cl(L)Ru(mu-tppz)Ru(L)Cl](1-5) containing differently substituted beta-diketonato derivatives (1: L = 2,4-pentanedionato; 2: L = 3,5-heptanedionato; 3: L = 2,2,6,6-tetramethyl-3,5-heptanedionato; 4: L = 3-methyl-2,4-pentanedionato; 5: L = 3-ethyl-2,4-pentanedionato) as ancillary ligands (L) were synthesized and studied by spectroelectrochemistry (UV-Vis-NIR, electron paramagnetic resonance (EPR)). X-ray structural characterisation revealed anti (1, 2, 5) or syn (3) configuration as well as non-planarity of the bis-tridentate tppz bridge and strong d pi(Ru-II) -> pi*(pyrazine, tppz) back-bonding. The widely separated one-electron oxidation steps, (RuRuII)-Ru-II/(RuRuIII)-Ru-II and (RuRuIII)-Ru-II/(RuRuIII)-Ru-III, result in large comproportionation constants (K-c) of >= 10(10) for the mixed-valent intermediates. The syn-configurated 3(n) exhibits a particularly high K-c of 10(12) for n = 1+, accompanied by density functional theory (DFT)-calculated minimum Ru-N bond lengths for this (RuRuIII)-Ru-II intermediate. The electrogenerated mixed-valent states 1(+)-5(+) exhibit anisotropic EPR spectra at 110 K with average values < g > of 2.304-2.234 and g anisotropies Delta g = g(1)-g(3) of 0.82-0.99. Metal-to-metal charge transfer (MMCT) absorptions occur for 1(+)-5(+) in the NIR region at 1660 nm-1750 nm (epsilon approximate to 2700 dm(3) mol(-1) cm(-1), Delta nu(1/2) approximate to 1800 cm(-1)). DFT calculations of 1(+) and 3(+) yield comparable Mulliken spin densities of about 0.60 for the metal ions, corresponding to valence-delocalised situations (Ru-2.5)(2). Rather large spin densities of about -0.4 were calculated for the tppz bridges in 1(+) and 3(+). The calculated electronic interaction values (V-AB) for 1(+)-5(+) are about 3000 cm(-1), comparable to that for the Creutz-Taube ion at 3185 cm(-1). The DFT calculations predict that the (RuRuIII)-Ru-III forms in 12(+)-52(+) prefer a triplet (S = 1) ground state with Delta E (S = 0 - S = 1) similar to 5000 cm(-1). One-electron reduction takes place at the tppz bridge which results in species [Cl(L)Ru-II(mu-tppz(.-)) Ru-II(L)Cl](-) (1(.-)-3(.-), 5(.-)) which exhibit free radical-type EPR signals and NIR transitions typical of the tppz radical anion. The system 4(n) is distinguished by lability of the Ru-Cl bonds.